2009
DOI: 10.1016/j.jmmm.2009.02.010
|View full text |Cite
|
Sign up to set email alerts
|

In-situ formation of barium ferrite in iron-doped “tetragonal tungsten bronze”: Elaboration of room temperature multiferroic composites

Abstract: To cite this version:Elias Castel, Michaël Josse, François Roulland, Dominique Michau, Lydia Raison, et al.. In-situ formation of barium ferrite in iron-doped "tetragonal tungsten bronze": Elaboration of room temperature multiferroic composites. Journal of Magnetism and Magnetic Materials, Elsevier, 2009, 321 (11)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…In recent years, the research dedicated to novel TTB ferroelectric and ferroelectric-related (i.e., relaxors) materials has undergone a revival, with Ba 6 FeNb 9 O 30 (BFNO) as a starting point; many related compositions [28][29][30][31] or solid solutions, usually containing lanthanides [32][33][34][35][36], were studied. Arnold and Morrison [5], and subsequently Liu et al [37], showed that these compounds display relaxor-type behaviour [38][39][40], with the peak maxima in the dielectric permittivity occurring in the temperature range 130-150 K. Earlier data indicated that BFNO is not electrically homogeneous [34], with oxygen vacancy gradients due to the variable oxidation state of Fe (Fe 3?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the research dedicated to novel TTB ferroelectric and ferroelectric-related (i.e., relaxors) materials has undergone a revival, with Ba 6 FeNb 9 O 30 (BFNO) as a starting point; many related compositions [28][29][30][31] or solid solutions, usually containing lanthanides [32][33][34][35][36], were studied. Arnold and Morrison [5], and subsequently Liu et al [37], showed that these compounds display relaxor-type behaviour [38][39][40], with the peak maxima in the dielectric permittivity occurring in the temperature range 130-150 K. Earlier data indicated that BFNO is not electrically homogeneous [34], with oxygen vacancy gradients due to the variable oxidation state of Fe (Fe 3?…”
Section: Introductionmentioning
confidence: 99%
“…Arnold and Morrison [5], and subsequently Liu et al [37], showed that these compounds display relaxor-type behaviour [38][39][40], with the peak maxima in the dielectric permittivity occurring in the temperature range 130-150 K. Earlier data indicated that BFNO is not electrically homogeneous [34], with oxygen vacancy gradients due to the variable oxidation state of Fe (Fe 3? /Fe 2?…”
Section: Introductionmentioning
confidence: 99%
“…By using the wet-chemical processing, in situ synthesis of multiferroic composites has been achieved and a three times larger magnetoelectric (ME) voltage coefficient was observed in the in situ synthesized samples [10]. The in situ synthesis of multiferroic composite was reported by Josse et al in Ba 2 LnFeNb 4 O 15 (Ln = rare earth) system [20,21].…”
Section: Introductionmentioning
confidence: 97%
“…This rich diversity of elements which can be incorporated into the TTB structure allows for compositional tuning that has been exploited for development of new phases [13,19] ranging from ferroelectrics [20][21][22] to microwave dielectrics [23,24] and to ionic conductors [25]. During the last few years, the research dedicated to novel TTB ferroelectric and ferroelectric-related materials resurrected [15][16][17][18][19][20][21][22][26][27][28][29][30][31], with the Ba 6 FeNb 9 O 30 (BFNO) [32][33][34][35] as starting point. Earlier data reported that BFNO is ferroelectric with T C values either in the range 133-138 K [36] or 570-583 K [37,38], however being not electrically homogeneous [29] and with oxygen vacancy gradients due to the variable oxidation state of Fe (Fe 3+ /Fe 2+ ); both low temperature dielectric spectroscopy and high temperature impedance spectroscopy measurements indicated more electroactive regions than anticipated [16].…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, the research dedicated to novel TTB ferroelectric and ferroelectric-related materials resurrected [15][16][17][18][19][20][21][22][26][27][28][29][30][31], with the Ba 6 FeNb 9 O 30 (BFNO) [32][33][34][35] as starting point. Earlier data reported that BFNO is ferroelectric with T C values either in the range 133-138 K [36] or 570-583 K [37,38], however being not electrically homogeneous [29] and with oxygen vacancy gradients due to the variable oxidation state of Fe (Fe 3+ /Fe 2+ ); both low temperature dielectric spectroscopy and high temperature impedance spectroscopy measurements indicated more electroactive regions than anticipated [16]. investigated by temperature-dependent powder neutron diffraction (TDPND) and by dielectric spectroscopy (DS); the confirmation of the phase formation and the crystallographic identification, but also the relaxor dielectric properties of these dense ceramic materials were already reported [39].…”
Section: Introductionmentioning
confidence: 99%